2015
DOI: 10.1016/j.neuropsychologia.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Beyond words: Pragmatic inference in behavioral variant of frontotemporal degeneration

Abstract: When the message of a speaker goes beyond the literal or logical meaning of the sentences used, a pragmatic inference is required to understand the complete meaning of an utterance. Here we study one example of pragmatic inference, called scalar implicature. Such an inference is required when a weaker term “some” is used in a sentence like “Some of the students passed the exam” because the speaker presumably had a reason not to use a stronger term like “all”. We investigated the comprehension of scalar implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Previous studies have classified the participants into pragmatic and semantic responders [Bott and Noveck, ; Noveck and Posada, ; Tavano, ]. Response distribution across participants in terms of subjective mismatch rating (mean across trials) under the strong and the weak implicature mismatch condition are shown in Supporting Information Figure S1A (see Supporting Information Materials), suggesting no clear distinction of logical and pragmatic responder in our participants group [Spotorno et al, ]. Performance data showing the rating distribution across trials based on all participants in six critical conditions can be found in Supporting Information Figure S1B (see Supporting Information Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have classified the participants into pragmatic and semantic responders [Bott and Noveck, ; Noveck and Posada, ; Tavano, ]. Response distribution across participants in terms of subjective mismatch rating (mean across trials) under the strong and the weak implicature mismatch condition are shown in Supporting Information Figure S1A (see Supporting Information Materials), suggesting no clear distinction of logical and pragmatic responder in our participants group [Spotorno et al, ]. Performance data showing the rating distribution across trials based on all participants in six critical conditions can be found in Supporting Information Figure S1B (see Supporting Information Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Pragmatic difficulties are reported also in mental illness, affecting the domains of figurative language and conversation ( Bambini et al, 2016a ), as well as scalars ( Wampers et al, 2017 ). Also neurological patients are impaired with pragmatics, in figurative language and discourse ( Bambini et al, 2016b ; Carotenuto et al, 2018 ), as well as in scalar inferences ( Spotorno et al, 2015 ). All these populations exhibit impairment in other cognitive domains too.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural variant of frontotemporal dementia (bvFTD) is the most frequent clinical form of frontotemporal lobar degeneration and the medial frontal cortex was identified as the brain region mainly affected in bvFTD (Schroeter et al 2008). An interesting and novel area of research in bvFTD is the analysis of inference processes in communication, such as pragmatic and intention processing (Kipps et al 2009;Shany-Ur et al 2012;Spotorno et al 2015). Impairment in the comprehension of insincere communication, such as sarcasm and lie processing, has been found in patients with bvFTD compared to both patients with Alzheimer's disease and healthy controls (Kipps et al 2009;Shany-Ur et al 2012).…”
Section: Neurodegenerative Studiesmentioning
confidence: 99%
“…A brain imaging analysis specifically linked the bvFTD patients' sarcasm impairment to atrophy in the medial and lateral orbitofrontal cortex (Kipps et al 2009). Further support derives from the study of Spotorno et al (2015), who found impairment in processing of pragmatic inference, such as scalar implicature. These authors pointed out a deficit in patients with bvFTD in producing alternative interpretations beyond a logical reading, and linked this deficit particularly to atrophy in ventromedial PFC.…”
Section: Neurodegenerative Studiesmentioning
confidence: 99%